Inhibition of the initiation of translation by a factor isolated from Escherichia coli cells. - Clark, V L (1980)
A low molecular weight factor isolated from Escherichia coli cells was found to inhibit protein synthesis in vitro directed by RNA of bacteriophage R-17. The factor also inhibited poly(U)-directed translation, but higher concentrations were required. When the factor was added after R-17 RNA-directed translation was initiated, the onset of inhibition was delayed. Initiation-independent translation of polysomes was not inhibited. The factor inhibited the binding of N-formylmethionyl-tRNAfMet to 70S ribosomes to form the 70S initiation complex, and it released the N-flrmylmethionyl-tRNAfMet from preformed complexes. The factor did not prevent the formation of N-formylmethionylpuromycin. It was concluded that the factor inhibits specifically the initiation of translation.